Print Pantas / Nur Aida Syamimi Wan Yahaya - Nur Aida Syamimi, Wan Yahaya (2020)
Print Pantas is stand for printing services and how fast produce and delivered the product to customer. The vision of this store is to provides the most dependable support, from initial contact to after-sales. While the mission is to fulfil customer needs by being a reliable printing service provider to form lasting relationship with them. It is planned to locate the business at Lot 597, Jalan Terentang, 71300 Rembau, Negeri Sembilan. This store is starting on a rented building to save up cost for a starter. In this store, there are 3 staff which is General Manager, Marketing Manager and delivery boy. All equipment and furniture that needed has been analysed and total the cost. Our targeted customer are students, workers and people live in this area. And the most common will came to store is students due to lot of assignment or homework that need to be print. Marketing strategies that used is business card, online promotion and signboard. To start up printing business, there are various materials that needed such as paper, comb ring, laminate paper, pvc sheet and others. While for equipment, there are printer, photocopy machine, laminator and binding machine. This is the common material and equipment that need to have in the store. Last but not least, financial plan where we need to predict it accordingly so there will be no loss suffer in future. A cash flow statement is to identify whether the business is beneficial or a deficit. If the cash flow is deficit, we need to construct a new plan in order to get a good and beneficial business.